Menguji Kesiapan Belajar Siswa Berbasis High Order Thinking Skill di Indonesia - Suharno Suharno; Muhammad Akhyar; Nugroho Agung Pambudi; Roemintoyo Roemintoyo; Sukatiman Sukatiman; Chundakus Habsya; Budi Tri Cahyono (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2022)
Even though HOTS-based learning has been implemented since 2018, students' readiness has not been tested. This study aims to test the willingness of students to learn based on HOTS in Indonesia. Readiness is reviewed based on the 4C criteria: critical thinking, creative, communicative, and collaborative. This study uses a descriptive quantitative approach. The sample was selected by random cluster sampling of 2.645 Indonesian students. The test method uses a questionnaire and observation. Data were taken by using observation, interview, and questionnaire techniques. The results show that students look active during discussions but still find it challenging to develop their creativity to solve problems. In quizzes, students should start to get used to the thinking process at levels C4 to C6, but students still choose C1 to C3. This study concludes that students are ready for criteria C1 to C3 and unprepared for learning at levels C4 to C6. Students need intense coaching and mentoring to support the successful implementation of HOTS-based learning.